2023
DOI: 10.1002/ejlt.202300010
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein aggregates‐alginate composite gel for astaxanthin‐chia oil encapsulation

Abstract: Chia oil (rich in omega-3 fatty acids) and astaxanthin are associated with various benefits for human health. However, their low solubility and poor stability reduce their direct use as bioactive compounds. Its encapsulation within the appropriate material can be a solution in this case. This work evaluated the effect of whey protein aggregates (WPA) on the storage stability of chia oil-astaxanthin blends encapsulated in alginate gel beads. Bead characteristics and the stability of encapsulated bioactive compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…100SA beads released 83.46 ± 1.07% and 56.10 ± 3.20%, while 25WPA75SA beads released 90.04 ± 2.85 and 63.01 ± 2.43% of AX and ω‐3, respectively. In a previous study (Espinaco et al, 2023), 100SA beads showed a smaller size compared to 25WPA75SA beads (2.08 ± 0.04 mm and 2.19 ± 0.07 mm, respectively). The results obtained in this work showed that this small difference in size did not affect the percentage of release of the encapsulated bioactive compounds.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…100SA beads released 83.46 ± 1.07% and 56.10 ± 3.20%, while 25WPA75SA beads released 90.04 ± 2.85 and 63.01 ± 2.43% of AX and ω‐3, respectively. In a previous study (Espinaco et al, 2023), 100SA beads showed a smaller size compared to 25WPA75SA beads (2.08 ± 0.04 mm and 2.19 ± 0.07 mm, respectively). The results obtained in this work showed that this small difference in size did not affect the percentage of release of the encapsulated bioactive compounds.…”
Section: Resultsmentioning
confidence: 69%
“…Emulsions were obtained according to Espinaco et al (2023). Briefly, solutions of wall materials were obtained by dispersing SA (2% w/w) and whey protein concentrate (WPC) (8% w/w) in ultrapure water.…”
Section: Preparation Of Emulsionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of encapsulation by extrusion/reticulation is simple and attractive and enables the formation of spherical particles at room temperature without the use of organic solvents, heat or vigorous agitation. In this process, the active substance can be physically or chemically entrapped and coupled with the polymers [ 2 , 4 , 5 ]. Nevertheless, WP microparticles (MP) rapidly release the active compound in simulated gastric and intestinal media, leading to nonoptimal biopharmaceutical behavior [ 6 ].…”
Section: Introductionmentioning
confidence: 99%